Exploring the variables that influences world-class warehouse performance: The case of PKT Logistics (Penang) Sdn. Bhd. - Ismail, Azril; Tan, Mary Poh Li; Ismail, Nor Atiqah; Tan, Pei Chin (2015)
“What you measure is what you get” is a favorite aphorism from many management writers.An efficient and effective warehousing that focused in logistics management and supply chain that would bring critical bottom-line role for companies worldwide.World-class warehouse performance referred as how the warehousing applied state-of-the-art tools,metrics and methodologies to increase the effectiveness, accuracy and overall productivity of warehousing operations.A success or failure warehouse not only depends on the ability where they adapt into market requirements but also need focused on the efficiency of the elements in green warehousing management, warehouse layout design, warehouse management system and safety climate.However, in the warehouse performance also interconnected between each other’s where the issue can be done in a holistic way by the parallel with new structures and redefining responsibilities boundaries. The present portion of the study is exploring the variables that influence world-class warehouse performance towards PKT Logistics (Penang) Sdn Bhd.A set of the questionnaire has been distributed to the employees of PKT Logistics (Penang) Sdn Bhd.The value of Cronbach’s alpha in reliability analysis for overall DV and IV is .946. Through the result get of correlation, the researcher can conclude that there is a significant relationship between world-class warehouse performance and four predictors’ variables which are green warehouse management, warehouse layout design, warehouse management system and safety climate.The finding explored was believed to establish more systematic aspect to ensure a better warehouse performance in the world-class level.